Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Penggunaan Teknologi Keuangan terhadap Pengelolaan Keuangan UMKM - Ma'rifatun Nisa; Gunawan Aji (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
MSMEs often face challenges in financial management due to limited understanding of accounting and poor finance due to lack of information. The purpose of this study is to see how the use of financial technology, financial inclusion, and financial literacy affect the financial management practices of MSMEs in Tegal Regency. A quantitative approach was used, by surveying 100 MSME participants selected through a simple random sampling technique for probability sampling. Eviews 13 software was used in the multiple linear regression analysis of primary and secondary data. The study shows that financial literacy and the use of financial technology have a significant impact on the overall financial management of MSMEs, while financial inclusion has no significant impact. However, the three factors have a significant impact when viewed together. The results show the importance of improving financial literacy and the use of financial technology, and that additional strategies are needed to improve how financial inclusion affects MSMEs.